Efeitos de poluentes do ar e doenças respiratórias utilizando dados estimados por modelo matemático - Roman, Vanessa Villalta Lima [UNESP]; de Carvalho, João Andrade [UNESP]; Nascimento, Luiz Fernando; Cesar, Ana Cristina G. (Instituto de Pesquisas Ambientais em Bacias Hidrograficas (IPABHi), 2015)
This study used a mathematical model to associate estimated concentrations of air pollutants with respiratory diseases. Admission data were obtained from Datasus relating to the hospitalization of residents in Taubaté due to respiratory diseases between 08/01/2011 and 07/31/2012. Values of the estimated air pollutant concentrations (CO, PM2.5, O3, NOx) were provided by the CATT-BRAMS (CPTEC-INPE) mathematical model. Daily data regarding temperature and relative humidity were obtained from CPTEC-INPE and used to calculate the apparent temperature, and then used to adjust the multipollutant model. The analysis used the generalized additive model Poisson regression, and lags of zero to five days. Three hundred and fifty two admissions occurred during the period analyzed. Exposures to oxides of nitrogen in the one day lag showed RR=1.046 (95% CI: 1.015-1.079) and at four days lag showed a RR=1.054 (95% CI: 1.054-1.196). The risk of hospitalization increases up to 17% when the concentrations of oxides of nitrogen increase by the amount of 3μg/m3. The use of estimated data by mathematical model identified an association between exposure to air pollutants and hospitalization due to respiratory diseases, validating the use of this model in cities where there are no air pollutant measuring stations.
Effects of air pollutants on respiratory diseases using estimated values by mathematical modelling of simulation
Keywords: Air pollution; Mathematical model; Nitrogen dioxide